Project management office models: a review - Monteiro, António (2016)
Organizations are facing competitive and globalized markets, as well as constant environmental changes that often require an organizational restructuring of the business models in order to boost performance. Project management practices can help to achieve strategic goals and increase value of projects in organizations. The Project Management Office (PMO) is an organizational structure created in order to promote and improve project management practice, by adopting appropriate methodologies to achieve high levels of efficiency and effectiveness. In recent years several models and functions of PMO have been proposed by many authors, varying from the PMO with a sole function of reporting project execution, to the one who participates in the definition of organizational strategies. The main purpose of this article is to present a review of the typologies of PMO. Since the importance of PMO is increasing in organizations, the results of this work are useful to provide guidance to organizations on implementing or restructuring their own PMO.